Preparation method of packaging material

By wrapping brominated polystyrene particles with silica and grafting the lipophilic group, the problems of poor flammability and compatibility of polystyrene plastics were solved, and packaging materials with high flame retardant properties, transparency and mechanical properties were prepared.

CN119613881APending Publication Date: 2025-03-14LINYI LUOHUI PACKAGING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933316.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Polystyrene plastics have poor flammability and poor compatibility between brominated polystyrene and polystyrene, resulting in discoloration and mechanical properties of the material, limiting its application in areas with high fire safety requirements.

Method used

Packaging materials with flame retardant properties and high transparency were prepared by wrapping brominated polystyrene particles with silica and grafting lipophilic groups to improve their compatibility and fluidity with polystyrene.

Benefits of technology

It effectively improves the flame retardant properties and transparency of polystyrene plastics, while maintaining the mechanical properties of the material, solving the discoloration and compatibility problems caused by the addition of brominated polystyrene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210889730000081
    Figure BDA0005210889730000081
Patent Text Reader

Abstract

The invention relates to a preparation method of a material, in particular to a preparation method of a packaging material. According to the invention, the problems of compatibility between brominated polystyrene and polystyrene and color change of polystyrene plastic caused by brominated polystyrene are solved by carrying out silicon dioxide wrapping on the flame retardant brominated polystyrene particles, and the fluidity of the polystyrene plastic is further ensured by grafting oleophylic groups.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a material, and in particular to a method for preparing a packaging material. Background Art

[0002] Polystyrene (PS) is a widely used thermoplastic plastic that occupies an important position in the field of packaging materials due to its excellent transparency, good processing performance and relatively low cost. From food packaging, electronic product packaging to daily consumer product packaging, polystyrene plastic meets the needs of different industries with its diverse forms and excellent performance. Its high transparency makes the product display effect excellent and easy to attract consumers' attention; at the same time, its good processing performance enables polystyrene to easily adapt to various molding processes, such as injection molding, blow molding, extrusion, etc., providing packaging designers with a broad creative space. However, a significant disadvantage of polystyrene is its flammability, which to a certain extent limits its application in certain fields with high fire safety requirements.

[0003] In order to improve the flame retardancy of polystyrene plastics, the industry often adopts the method of adding flame retardants. Brominated polystyrene (BPS) is a common flame retardant and has a significant flame retardant effect because it contains bromine. Bromine can release halogen free radicals during the combustion process, interfere with the combustion chain reaction, and thus effectively slow down or prevent the spread of fire. However, adding brominated polystyrene directly to polystyrene plastics often brings a series of problems. First, the addition of brominated polystyrene often causes polystyrene plastics to discolor, affecting its appearance quality. Secondly, due to the poor compatibility between brominated polystyrene and polystyrene, the two are prone to stratification and agglomeration during the mixing process, which not only affects the uniformity of the material, but also may reduce its mechanical properties. These problems seriously restrict the widespread application of brominated polystyrene as a flame retardant in polystyrene plastics.

[0004] In response to the problems of adding brominated polystyrene directly to polystyrene plastic, the applicant proposed an innovative solution: first wrap the brominated polystyrene particles with silica, and then add them to the polystyrene plastic. This wrapping treatment not only effectively improves the compatibility between brominated polystyrene and polystyrene, allowing the two to be mixed more evenly, but also the brominated polystyrene is not easy to migrate out under the protection of the silica wrapping layer, thereby avoiding the problem of material discoloration and maintaining the high transparency of the polystyrene plastic. However, the applicant also found that although this method of adding brominated polystyrene wrapped with silica solves the compatibility and discoloration problems, it affects the fluidity of polystyrene plastic, thereby affecting the mechanical properties of the packaging material. Changes in fluidity may affect the molding efficiency during the processing and the final quality of the product, so how to balance the relationship between flame retardant properties and fluidity has become a new problem that needs to be solved urgently. Summary of the invention

[0005] In response to the above technical problems, the present application provides a method for preparing a polystyrene packaging material, which solves the compatibility between brominated polystyrene and polystyrene and the problem of discoloration of polystyrene plastic caused by brominated polystyrene by coating flame retardant brominated polystyrene particles with silica, and further ensures the fluidity of polystyrene plastic by grafting lipophilic groups.

[0006] Specifically, the present invention provides a method for preparing a packaging material, which comprises the following basic steps:

[0007] a) dispersing brominated polystyrene (BPS) particles in a solvent and adding a surfactant to form a stable suspension;

[0008] b) adding a silica precursor and a catalyst to the suspension, causing the silica precursor to undergo hydrolysis and condensation reaction on the surface of the BPS particles under stirring, generating a silica (SiO2) shell layer in situ to tightly wrap the BPS particles; and performing solid-liquid separation and drying to obtain SiO2-wrapped BPS particles;

[0009] c) grafting lipophilic groups onto SiO2-encapsulated BPS particles;

[0010] d) mixing SiO2-BPS composite particles grafted with lipophilic groups, polystyrene (PS) and at least one additive to prepare a composite material by melt blending;

[0011] e) cooling, pelletizing and drying the composite material, and preparing the final packaging material through a molding process selected from the group consisting of blow molding, injection molding and casting.

[0012] Preferably, in step a), the solvent is ethanol or water, and the surfactant is selected from at least one of anionic surfactants selected from sodium dodecyl sulfate (SDS), cationic surfactants selected from hexadecyltrimethylammonium bromide (CTAB), nonionic surfactants selected from polyethylene glycol octylphenyl ether (Triton X-100) or zwitterionic surfactants, and the added mass ratio of the surfactant to brominated polystyrene is 1-5:100.

[0013] Preferably, in step b), the silicon dioxide precursor is selected from one of methyl orthosilicate or ethyl orthosilicate, and the added mass ratio of the silicon dioxide precursor to brominated polystyrene is 1-10:1.

[0014] Preferably, in step b), the catalyst is selected from at least one of aqueous ammonia, hydrochloric acid, sodium hydroxide or potassium hydroxide solution, and its added amount is 1%-10% of the amount of the silica precursor, the reaction temperature is controlled in the range of 40-80°C, the reaction time is 5-20h, and the stirring speed is 5-500rpm.

[0015] Preferably, in step c), the grafted lipophilic groups are treated by mixing the SiO2-BPS composite particles with at least one monomer selected from methyl methacrylate (MMA), styrene, butyl acrylate, ethyl methacrylate or propyl methacrylate, heating to 80-120°C under nitrogen protection, reacting for 2-6 hours, and then removing the ungrafted monomers and solvent by washing, filtering and drying.

[0016] Preferably, in step d), the additive comprises at least one component selected from the following types:

[0017] Antioxidant: selected from one of hindered phenol antioxidants, phosphite antioxidants or thioester antioxidants;

[0018] UV stabilizer: one or more selected from benzotriazole UV absorbers, benzophenone UV absorbers or hindered amine light stabilizers;

[0019] Plasticizer: one or more selected from phthalate plasticizers, aliphatic dibasic acid ester plasticizers or epoxidized soybean oil;

[0020] Anti-slip agent: one or more selected from diatomaceous earth, talcum powder or micro-silica gel;

[0021] Antistatic agent: one or more selected from quaternary ammonium salt antistatic agents, fatty acid ester antistatic agents or polyether antistatic agents;

[0022] Pigment or dye: one or more selected from inorganic pigments, organic pigments or dyes;

[0023] Biodegradation accelerator: one or more selected from starch, cellulose or their derivatives.

[0024] Preferably, the amount of antioxidant added is 0.1%-5% of the total weight of the composite material, the amount of UV stabilizer added is 0.1%-3% of the total weight of the composite material, the amount of plasticizer added is 1%-10% of the total weight of the composite material, the amount of anti-slip agent and antistatic agent added is each 0.1%-2% of the total weight of the composite material, the amount of pigment or dye added is adjusted according to the desired color depth, and the amount of biodegradation accelerator added is determined according to the biodegradation target of the material.

[0025] Preferably, in step d), the mixing mass ratio of SiO2-BPS composite particles grafted with lipophilic groups, PS and additives is (5-20):(70-90):5-15, and the melt blending is carried out in a twin-screw extruder, the extruder temperature is controlled in the range of 180-220°C, and the screw speed is 200-400rpm.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] Firstly, the present invention solves the compatibility between brominated polystyrene and polystyrene and the problem of discoloration of polystyrene plastic caused by brominated polystyrene by coating the flame retardant brominated polystyrene particles with silica, and further ensures the fluidity of the polystyrene plastic by grafting lipophilic groups, while the silica not coating the brominated polystyrene can also be used as an additive for polystyrene packaging materials.

[0028] Secondly, the present invention ensures that the silicon dioxide produced by hydrolysis is wrapped on the surface of the polystyrene by in-situ polymerization of silicon dioxide and by controlling the stirring speed and reaction conditions. DETAILED DESCRIPTION

[0029] Example 1

[0030] A method for preparing a polystyrene packaging material, the specific steps are as follows:

[0031] a) dispersing 100 g of brominated polystyrene (BPS) particles in 500 mL of ethanol, adding 3 g of sodium dodecyl sulfate (SDS) as a surfactant, and forming a stable suspension by ultrasonic dispersion and mechanical stirring;

[0032] b) Slowly drop 10g of tetraethyl orthosilicate as a silica precursor into the above suspension, and add 1g of ammonia water as a catalyst. The mixture is stirred at 100rpm at 50°C for 10 hours to allow the silica precursor to undergo hydrolysis and condensation reactions on the surface of the BPS particles, and an in-situ silica (SiO2) shell is generated to tightly wrap the BPS particles. After the reaction is completed, solid-liquid separation is achieved by centrifugation, and the mixture is dried into solid particles;

[0033] c) mixing the solid particles with 5 g of methyl methacrylate (MMA) monomer, heating to 100° C. under nitrogen protection, reacting for 4 hours, and then removing the ungrafted monomers and solvent by washing, filtering and drying to obtain SiO2-BPS composite particles grafted with lipophilic groups;

[0034] d) Mixing the SiO2-BPS composite particles grafted with lipophilic groups with 850 g of polystyrene (PS) and an additive consisting of 5 g of BHT, 5 g of a benzotriazole ultraviolet absorber, 20 g of a phthalate plasticizer, 5 g of a diatomaceous earth anti-slip agent, and 5 g of a stearyl trimethyl quaternary ammonium hydrochloride antistatic agent. Melt-blending the mixture in a twin-screw extruder, with the extruder temperature controlled at 200° C. and the screw speed at 300 rpm, to obtain a composite material;

[0035] e) cooling, pelletizing and drying the composite material, and obtaining the final packaging material through a casting process.

[0036] Example 2

[0037] A method for preparing a polystyrene packaging material, the specific steps are as follows:

[0038] a) dispersing 100 g of brominated polystyrene (BPS) particles in 500 mL of ethanol, adding 3 g of sodium dodecyl sulfate (SDS) as a surfactant, and forming a stable suspension by ultrasonic dispersion and mechanical stirring;

[0039] b) Slowly drop 10g of methyl orthosilicate as a silica precursor into the above suspension, and add 1g of ammonia water as a catalyst. The mixture is stirred at 100rpm at 50°C for 10 hours to hydrolyze and condense the silica precursor on the surface of the BPS particles, and a silica (SiO2) shell is generated in situ to tightly wrap the BPS particles. After the reaction, solid-liquid separation is achieved by centrifugation, and the mixture is dried into solid particles;

[0040] c) mixing the solid particles with 5 g of methyl methacrylate (MMA) monomer, heating to 100° C. under nitrogen protection, reacting for 4 hours, and then removing the ungrafted monomers and solvent by washing, filtering and drying to obtain SiO2-BPS composite particles grafted with lipophilic groups;

[0041] d) Mixing the SiO2-BPS composite particles grafted with lipophilic groups with 850 g of polystyrene (PS) and an additive consisting of 5 g of BHT, 5 g of a benzotriazole ultraviolet absorber, 20 g of a phthalate plasticizer, 5 g of a diatomaceous earth anti-slip agent, and 5 g of a stearyl trimethyl quaternary ammonium hydrochloride antistatic agent. Melt-blending the mixture in a twin-screw extruder, with the extruder temperature controlled at 200° C. and the screw speed at 300 rpm, to obtain a composite material;

[0042] e) cooling, pelletizing and drying the composite material, and obtaining the final packaging material through a casting process.

[0043] Comparative Example 1

[0044] a) Slowly drop 10g of tetraethyl orthosilicate as a silica precursor into 500mL of ethanol, and add 1g of ammonia water as a catalyst. The reaction is carried out at 50°C and a stirring speed of 100rpm for 10 hours to generate silica particles from the silica precursor in situ. After the reaction is completed, solid-liquid separation is achieved by centrifugation, and the mixture is dried into solid particles;

[0045] c) mixing the solid particles with 100 g of brominated polystyrene (BPS) particles and 5 g of methyl methacrylate (MMA) monomer, heating to 100° C. under nitrogen protection, reacting for 4 hours, and then removing the ungrafted monomers and solvent by washing, filtering and drying to obtain particles grafted with lipophilic groups;

[0046] d) Mixing the above-mentioned particles grafted with lipophilic groups with 850 g of polystyrene (PS) and an additive consisting of 5 g of BHT, 5 g of a benzotriazole ultraviolet absorber, 20 g of a phthalate plasticizer, 5 g of a diatomaceous earth anti-slip agent, and 5 g of a stearyl trimethyl quaternary ammonium hydrochloride antistatic agent. Melt-blending the mixture in a twin-screw extruder, with the extruder temperature controlled at 200° C. and the screw speed at 300 rpm, to obtain a composite material;

[0047] e) cooling, pelletizing and drying the composite material, and obtaining the final packaging material through a casting process.

[0048] Comparative Example 2

[0049] A method for preparing a polystyrene packaging material, the specific steps are as follows:

[0050] a) dispersing 100 g of brominated polystyrene (BPS) particles in 500 mL of ethanol, adding 3 g of sodium dodecyl sulfate (SDS) as a surfactant, and forming a stable suspension by ultrasonic dispersion and mechanical stirring;

[0051] b) Slowly drop 10g of tetraethyl orthosilicate as a silica precursor into the above suspension, and add 1g of ammonia water as a catalyst. The mixture is stirred at 100rpm at 50°C for 10 hours to allow the silica precursor to undergo hydrolysis and condensation reactions on the surface of the BPS particles, and an in-situ silica (SiO2) shell is generated to tightly wrap the BPS particles. After the reaction is completed, solid-liquid separation is achieved by centrifugation, and the mixture is dried into solid particles;

[0052] c) mixing the solid particles with 850 g of polystyrene (PS) and an additive consisting of 5 g of BHT, 5 g of a benzotriazole ultraviolet absorber, 20 g of a phthalate plasticizer, 5 g of a diatomaceous earth anti-slip agent, and 5 g of a stearyl trimethyl quaternary ammonium hydrochloride antistatic agent. The mixture was melt-blended in a twin-screw extruder, the extruder temperature was controlled at 200° C., and the screw speed was 300 rpm, to obtain a composite material;

[0053] e) cooling, pelletizing and drying the composite material, and obtaining the final packaging material through a casting process.

[0054] The packaging material samples of the above embodiments and comparative examples were subjected to characterization tests, and the characterization items included:

[0055] (1) Characterization of flame retardant properties

[0056] Characterization method: Limiting oxygen index (LOI) test

[0057] Characterization parameters: Limiting oxygen index value

[0058] Conditions: Tested in accordance with ASTM D2863, with standard sample size, room temperature, and increasing oxygen concentration until the sample continues to burn.

[0059] (2) Characterization method: melt flow rate (MFR) test

[0060] Characterization parameters: melt flow rate value (g / 10min)

[0061] Conditions: Tested according to ASTM D1238 standard, test temperature is 200℃, load is 2.16kg.

[0062] (3) Transparency Characterization

[0063] Characterization method: transmittance test

[0064] Characterization parameters: transmittance value (%)

[0065] Conditions: Use a transmittance tester, the test sample thickness is 1mm, and the wavelength is 550nm.

[0066] (4) Mechanical properties characterization

[0067] Characterization method: tensile test

[0068] Characterization parameters: tensile strength (MPa) and elongation at break (%)

[0069] Conditions: Tested in accordance with ASTM D638 standard, test speed is 50mm / min.

[0070] The specific results are shown in Table 1:

[0071] Table 1 Characterization data of different embodiments and comparative examples

[0072]

[0073] Based on the above content, it can be seen that the packaging material prepared by the method of the present invention can improve parameters such as light transmittance, tensile strength and elongation at break of the packaging material while ensuring flame retardant properties, and has high application value.

Claims

1. A method for preparing a packaging material, characterized in that: The basic steps include: a) dispersing brominated polystyrene (BPS) particles in a solvent and adding a surfactant to form a stable suspension; b) adding a silica precursor and a catalyst to the suspension, allowing the silica precursor to undergo hydrolysis and condensation reactions on the surface of the BPS particles under stirring, generating an in-situ silica (SiO2) shell layer to tightly wrap the BPS particles, and performing solid-liquid separation and drying to obtain SiO2-wrapped BPS particles; c) grafting lipophilic groups onto SiO2-encapsulated BPS particles; d) mixing SiO2-BPS composite particles grafted with lipophilic groups, polystyrene (PS) and at least one additive to prepare a composite material by melt blending; e) cooling, pelletizing and drying the composite material, and preparing the final packaging material through a molding process selected from the group consisting of blow molding, injection molding and casting.

2. The method for preparing a packaging material according to claim 1, characterized in that: In step a), the solvent is ethanol or water, and the surfactant is selected from at least one of anionic surfactants selected from sodium dodecyl sulfate (SDS), cationic surfactants selected from hexadecyltrimethylammonium bromide (CTAB), nonionic surfactants selected from polyethylene glycol octylphenyl ether (Triton X-100) or zwitterionic surfactants, and the added mass ratio of the surfactant to brominated polystyrene is 1-5:

100.

3. The method for preparing a packaging material according to claim 1, characterized in that: In step b), the silicon dioxide precursor is selected from one of methyl orthosilicate or ethyl orthosilicate, and the addition mass ratio of the silicon dioxide precursor to brominated polystyrene is 1-10:

1.

4. The method for preparing a packaging material according to claim 1, characterized in that: In step b), the catalyst is selected from at least one of ammonia water, hydrochloric acid, sodium hydroxide or potassium hydroxide solution, and its addition amount is 1%-10% of the amount of silica precursor, the reaction temperature is controlled in the range of 40-80°C, the reaction time is 5-20h, and the stirring speed is 5-500rpm.

5. The method for preparing a packaging material according to claim 1, characterized in that: In step c), the grafted lipophilic groups are treated by mixing the SiO2-BPS composite particles with at least one monomer selected from methyl methacrylate (MMA), styrene, butyl acrylate, ethyl methacrylate or propyl methacrylate, heating to 80-120°C under nitrogen protection, reacting for 2-6 hours, and then removing the ungrafted monomers and solvent by washing, filtering and drying.

6. The method for preparing a packaging material according to claim 1, characterized in that: In step d), the additive comprises at least one component selected from the following types: Antioxidant: selected from one of hindered phenol antioxidants, phosphite antioxidants or thioester antioxidants; UV stabilizer: one or more selected from benzotriazole UV absorbers, benzophenone UV absorbers or hindered amine light stabilizers; Plasticizer: one or more selected from phthalate plasticizers, aliphatic dibasic acid ester plasticizers or epoxidized soybean oil; Anti-slip agent: one or more selected from diatomaceous earth, talcum powder or micro-silica gel; Antistatic agent: one or more selected from quaternary ammonium salt antistatic agents, fatty acid ester antistatic agents or polyether antistatic agents; Pigment or dye: one or more selected from inorganic pigments, organic pigments or dyes; Biodegradation accelerator: one or more selected from starch, cellulose or their derivatives.

7. The method for preparing a packaging material according to claim 6, characterized in that: The amount of antioxidant added is 0.1%-5% of the total weight of the composite material, the amount of UV stabilizer added is 0.1%-3% of the total weight of the composite material, the amount of plasticizer added is 1%-10% of the total weight of the composite material, the amount of anti-slip agent and antistatic agent added is each 0.1%-2% of the total weight of the composite material, the amount of pigment or dye added is adjusted according to the required color depth, and the amount of biodegradation accelerator added is determined according to the biodegradation target of the material.

8. The method for preparing a packaging material according to claim 1, characterized in that: In step d), the mixing mass ratio of SiO2-BPS composite particles grafted with lipophilic groups, PS and additives is (5-20):(70-90):5-15, and melt blending is carried out in a twin-screw extruder. The extruder temperature is controlled in the range of 180-220°C and the screw speed is 200-400rpm.

9. A packaging material prepared according to the method for preparing a packaging material according to claim 1.